Lymph Node Metastasis in the Prognosis of Gastroenteropancreatic Neuroendocrine Tumors - Martin, Jacob A. (Pancreas, 2017)
OBJECTIVES: This study aimed to determine the prognostic utility of the extent of lymph node involvement in patients with gastroenteropancreatic neuroendocrine tumors (GEP-NETs) by analyzing population-based data. METHODS: Patients in the Surveillance, Epidemiology, and End Results (SEER) registry were identified with histologically confirmed, surgically resected GEP-NETs. We divided patients into three lymph node ratio (LNR) groups based on the ratio of positive lymph nodes to total lymph nodes examined: ≤0.2, >0.2–0.5, and >0.5. Disease-specific survival was compared according to LNR group. RESULTS: We identified 3,133 patients with surgically resected GEP-NETs. Primary sites included stomach (11% of the total), pancreas (30%), colon (32%), appendix (20%), and rectum (7%). Survival was worse in patients with LNRs of ≤0.2 (hazard ratio [HR], 1.5; 95% confidence interval [CI], 1.2–2.0), >0.2–0.5 (HR, 2.0; 95% CI, 1.6–2.5), and >0.5 (HR, 3.1; 95% CI, 2.5–3.9) compared to N0 patients. Ten-year disease-specific survival decreased as LNR increased from N0 (81%) to ≤0.2 (69%), >0.2–0.5 (55%), and >0.5 (50%). Results were consistent for patients with both low and high grade tumors from most primary sites. CONCLUSIONS: Degree of lymph node involvement is a prognostic factor at the most common GEP-NET sites. Higher LNR is associated with decreased survival.